2014
DOI: 10.1016/j.apmr.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for Everyone: A Randomized Controlled Trial of Project Workout on Wheels in Promoting Exercise Among Wheelchair Users

Abstract: Objective To compare the effectiveness of two home-based behavioral interventions to promote wheelchair users exercise adoption and maintenance over 12 months. Design Randomized controlled trial, with participants stratified into groups based on disability type (stable, episodic, progressive) and support partner availability. Setting Exercise occurred in participant preferred locations (e.g., home, recreation center), with physiological data collected at the university-based exercise lab. Participants On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 44 publications
2
60
1
1
Order By: Relevance
“…8,9 In agreement with other studies, interventions delivered by exercise professionals via SCIPA Com showed increased physical activity uptake and reduced expenses, while making these services available to others in the community. 8,21 The 'T3-SCI' course also provided exercise professionals with an opportunity to adapt their knowledge in health and fitness for clients with SCI. Their lack of experience with people with disabilities did not deter development of effective programs.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…8,9 In agreement with other studies, interventions delivered by exercise professionals via SCIPA Com showed increased physical activity uptake and reduced expenses, while making these services available to others in the community. 8,21 The 'T3-SCI' course also provided exercise professionals with an opportunity to adapt their knowledge in health and fitness for clients with SCI. Their lack of experience with people with disabilities did not deter development of effective programs.…”
Section: Discussionsupporting
confidence: 74%
“…18 The average improvement was remarkably higher in this study compared with similar programs that resulted in improvements between 17 and 155 min of LTPA per week. 8,9 This difference was possibly due to the alignment of exercise programs with the patient's expectations and capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…"necessitating wheelchair use for mobility outside the home." 61 Recognizing that the "International SCI Activity and Participation Basic Data Set" 62 includes the item "mobility moderate distances (10 to 100 m)" which is consistent with the relevant SCIM item (whereas items on indoor mobility and mobility outdoors >100 m are not included), we chose to define wheelchair users as participants who stated to use a wheelchair at this item. This will facilitate future comparisons of our sample with samples of other studies.…”
Section: Discussionmentioning
confidence: 99%